PENGELOLAAN DESA WISATA BUMDES BERBASIS EKONOMI KREATIFDAN KEARIFAN LOKAL DI DESA KARANGREJO KECAMATAN PURWOSARI PASURUAN - Ratnawati, Susi; Prajitno, Nezha Tasmara (Jurnal ABDI Bhayangkara, 2023)
Pasuruan is very famous for its village earth tourism, there are lots of tourist attractions that are very unique in the eyes of visitors, because of that the surrounding community uses creativity innovation in building and creating tourism in the village environment to be able to take advantage of village resources by creating creativity, so that the village grows. Ef orts to empower the potential of the village need to be continued so that the quality of the village is better. Thus, the resources in the village, both natural resources and human resources, are very potential in the welfare of the community, by managing them well, the village will develop well. Therefore, progress towards innovation villages is currently very much needed, through mapping potential villages. This is so that village development focuses on the potential of each village. This mapping is very important so that the development process is very clear and in accordance with the targets desired by the community, so that it can be evaluated better. Villagedevelopment must be oriented towards increasing competitiveness and economic growth, strengthening institutional governance in the village more ef iciently and ef ectively. One of these ef orts is through an innovation program as an ef ort to improve community welfare through village-level development based on local wisdom, resource potential and the uniquenessof the village. There are four pillars in building a better and more attractive village, namely there are four, the first is public services, basic administrative services, education, and health. The second is agriculture, and livestock plantations, and science and technology. Third is MSMEs according to village potential and fourth is facilities and infrastructure, development by utilizing various integrated programs.